ФОРМУВАННЯ ІНТЕЛЕКТУАЛЬНИХ УМІНЬ У МОЛОДШИХ УЧНІВ У ПРОЦЕСІ ХУДОЖНЬОГО КОНСТРУЮВАННЯ (Педагогіка вищої та середньої школи, 2022)
Forming intellectual ability demands special conditions which helps child to overcome stresses, overstrain, uneasness,schools, fears, connected with the process o f teaching which contributes to propitious climate for fitted developing of pupils personality in the primary school.